2015
DOI: 10.1016/j.neuroimage.2015.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Orientation dependence of magnetization transfer parameters in human white matter

Abstract: Quantification of magnetization-transfer (MT) experiments is typically based on a model comprising a liquid pool "a" of free water and a semisolid pool "b" of motionally restricted macromolecules or membrane compounds. By a comprehensive fitting approach, high quality MT parameter maps of the human brain are obtained. In particular, a distinct correlation between the diffusion-tensor orientation with respect to the B0-magnetic field and the apparent transverse relaxation time, T2(b), of the semisolid pool (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
83
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 58 publications
10
83
1
Order By: Relevance
“…T 2 B measurements obtained in this study are highly consistent with the literature data based on the analysis with the Super-Lorentzian lineshape (Morrison and Henkelman, 1995; Sled and Pike, 2001; Yarnykh, 2002; Sled et al, 2004; Stanisz et al, 2005; Underhill et al, 2009; Levesque et al, 2010; Pohmann et al, 2011; Underhill et al, 2011; Samsonov et al, 2012; Yarnykh, 2012; Thiessen et al, 2013; Mossahebi et al, 2014; Pampel et al, 2015; Varma et al, 2015b) and do not suggest any field dependence of this parameter. Generally, T 2 B values demonstrate minimal distinctions between WM and GM and a narrow range of variations (typically about 8–12 μs) in the brain.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…T 2 B measurements obtained in this study are highly consistent with the literature data based on the analysis with the Super-Lorentzian lineshape (Morrison and Henkelman, 1995; Sled and Pike, 2001; Yarnykh, 2002; Sled et al, 2004; Stanisz et al, 2005; Underhill et al, 2009; Levesque et al, 2010; Pohmann et al, 2011; Underhill et al, 2011; Samsonov et al, 2012; Yarnykh, 2012; Thiessen et al, 2013; Mossahebi et al, 2014; Pampel et al, 2015; Varma et al, 2015b) and do not suggest any field dependence of this parameter. Generally, T 2 B values demonstrate minimal distinctions between WM and GM and a narrow range of variations (typically about 8–12 μs) in the brain.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, T 2 B values demonstrate minimal distinctions between WM and GM and a narrow range of variations (typically about 8–12 μs) in the brain. Residual tissue contrast on T 2 B maps has been recently attributed to the directional dependence of this parameter in WM (Yarnykh, 2012; Pampel et al, 2015). The visual appearance of T 2 B maps of the rat brain at 11.7T (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous MT experiments have also reported a dependence of quantitative MT‐derived parameters (e.g. T 2B – T 2 of bound protons) on WM anisotropy . Hence, the results obtained here warrant further investigations in order to interpret the WM anisotropy effect on ihMT and to evaluate to what extent it is a potential confounder for ihMT quantification.…”
Section: Discussionsupporting
confidence: 61%
“…It is interesting to note that the NOE and MT values appear to be uncoupled in the corpus callosum, with the MT/NOE ratio varying between the truncus and the splenium and genu. Previous investigators have suggested that the truncus and genus have more myelinated axons than the splenium (31), so this may indicate a difference in sensitivity of the NOE and MT signals to myelination; alternatively, this result may relate to the previously reported dependence of MT on fiber orientation (20). In practice, a small positive APT pool was measured in all GM and WM ROIs.…”
Section: Discussionmentioning
confidence: 92%